Hydrochemical and isotopic characterization of the hydrological budget of a MAB Reserve: Mar Chiquita lagoon, province of Buenos Aires, Argentina - Glok Galli, Melisa (2014)
Mar Chiquita is a coastal lagoon located in the Argentine Buenos Aires province in South America. The aim of this study was to perform a hydrochemical and stable isotopes characterization in order to better the understanding of the hydrology of the Mar Chiquita lagoon’s catchment and its water budget. Groundwater samples were taken from 144 wells and 21 samples from main streams, and seven lagoon water samples were also collected. Chemical analyses were carried out using standard laboratory methods, and isotopic determinations were made through laser spectroscopy using a DLT-100 liquid–water isotope analyzer. Hydrochemical analysis permits a general classification of groundwater and streamwater as sodium bicarbonate waters, while the lagoon chemical composition shows an evolution toward seawater composition, from the north to its mouth, which is located southerly. Isotopic data show a source of aquifer recharge from rainfall and a groundwater domain into the streams’ flow. Three main components can be recognized as end members in a plot of electrical conductivity (EC) versus δ18O: seawater, streamwater and groundwater. Obtained EC values for groundwater in the discharge zone (EC average value = 3,516 μS/cm) allow minimizing its direct contribution and to take into consideration two dominating end members: streamwater and seawater. Mar Chiquita lagoon’s water falls close to the line between streamwater and seawater end members according to its EC and δ18O. The obtained seawater proportion for these samples ranges from 84 % in the lagoon’s mouth to around 0 % in the more distal area.